Cardiopulmonary resuscitation and first‐aid training of river users in Australia: A strategy for reducing drowning. (16th September 2018) - Peden, Amy E.; Franklin, Richard C.; Leggat, Peter A.
Abstract: Issue addressed: Rivers are a leading location for fatal drowning worldwide, often geographically isolated from timely medical assistance. Cardiopulmonary resuscitation (CPR) benefits drowning victims and those who suffer cardiac arrests. This study explored CPR and first‐aid training of river users in Australia. Methods: Adult river users (18+ years) were surveyed at four high‐risk river drowning sites. Respondents were asked the last time they undertook CPR (responses converted into: "CPR ever undertaken"—yes/no; and "CPR training current"—yes/no (training undertaken ≤12 months ago). Responses were explored by demographics and social determinants of health. Results: Of those surveyed (N = 688), 98.4% responded regarding CPR. Seventy‐five percent (74.9%) had undertaken CPR training previously. Females and 35‐ to 44‐year‐olds were more likely to have undertaken training ( P < 0.05). Males and older people (65+ years) were less likely to hold a current qualification ( P < 0.05). Major city residents reported a longer mean time (5.4 years) since last trained than remote and very remote locations (2.0 years). People in low socio‐economic areas had a shorter time since qualification current (5.8 years) than those in areas deemed high (7.2 years). Conclusion: Current CPR qualifications are important, particularly among those visiting high‐risk river drowning locations. System‐level, upstream strategies that should be explored include compulsory CPR training in secondary schools and linking CPR updates to motor vehicle licence renewals. So what?: Cardiopulmonary resuscitation is a vital component of multifaceted river drowning prevention. Social determinants of health, such as socio‐economic disadvantage and geographical isolation, were not barriers to participation or currency of qualification.